STRATEGY ANALYSIS OF HANDLING CIRCULATION AND ABUSE USING SWOT METHOD AT CLASS IIB RUTAN PRABUMULIH - Lusi Hertina; Umar Anwar (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This research is motivated by the increasing number of prisoners and convicts of narcotics crimes. So, it can grab the attention of the public and the government. This is based on several cases of narcotics trafficking that occurred in the correctional task force unit (UPT). The purpose of this study was to find out how the environmental conditions of the correctional task force unit (UPT) internally and externally in the strategy of dealing with drug trafficking in the Class IIB Rutan Prabumulih. This research is qualitative in nature which describes or describes the object under study and the observed phenomena on the phenomena that occur in the field. SWOT analysis is used to formulate service strategy. The results of the data management of the internal environmental strategy factors and the results of the external environmental strategy factor data management show that the condition of the prison organization is in a weak condition facing the challenges of narcotics trafficking in prisons. Therefore, the recommended strategy is a defensive or defensive strategy. Keywords: Drug Trafficking, Prisons, SWOT.